2013
DOI: 10.1016/j.neuint.2012.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Metals, oxidative stress and neurodegeneration: A focus on iron, manganese and mercury

Abstract: Essential metals are crucial for the maintenance of cell homeostasis. Among the 23 elements that have known physiological functions in humans, 12 are metals, including iron (Fe) and manganese (Mn). Nevertheless, excessive exposure to these metals may lead to pathological conditions, including neurodegeneration. Similarly, exposure to metals that do not have known biological functions, such as mercury (Hg), also present great health concerns. This reviews focuses on the neurodegenerative mechanisms and effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
285
1
16

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 480 publications
(316 citation statements)
references
References 316 publications
(450 reference statements)
14
285
1
16
Order By: Relevance
“…Nevertheless, to date it is still not clear why neurons show this enhanced bioavailability for Hg species. Considering brain areas, Hg species seem to persist in cerebellum and cortex in vivo [ 4,38). After long-term incubation for aJI Hg species, but especially for HgC1 2 , a strong increase in the lysosomal integrity was observed.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, to date it is still not clear why neurons show this enhanced bioavailability for Hg species. Considering brain areas, Hg species seem to persist in cerebellum and cortex in vivo [ 4,38). After long-term incubation for aJI Hg species, but especially for HgC1 2 , a strong increase in the lysosomal integrity was observed.…”
Section: Discussionmentioning
confidence: 97%
“…Dysregulation of CNS iron levels has been linked to several neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease, where current iron chelating therapeutics have been designed to block the redox-activity of iron and prevent its contribution to disease progression (Farina et al, 2013). Treatments to counteract the neurotoxic effects of iron and oxidative stress, and/or to promote astrocytic expression of MT may also potentially benefit MS patients.…”
Section: Discussionmentioning
confidence: 99%
“…31 Exposure to MeHg during early fetal development can cause neurodevelopmental injury at doses much lower than those affecting adult brain function. 32,33 Due to the early differentiation and growth of the choroid plexus compared to the subsequent vascularization in the developing brain, it has been suggested that in early development the main portal of molecular transfer from blood into the brain is via the choroid plexus and CSF rather than via the sparsely distributed View Article Online cerebral blood vessels. 34 Therefore, based on the demonstrated active efflux of MeHgCl and thiomersal out of the brain, the blood-CSF barrier might prevent the developing brain as well as the adult brain from further neurotoxic damage induced by the mercury compounds.…”
Section: Discussionmentioning
confidence: 99%